Design of a New Student Registration Information System Based on a Website Using the Agile Method - Zatin Niqotaini; Arafat Febriandirza; Esa Prakasa; Irman Hermadi (Fakultas Ilmu Komputer, 2026)
The application of information technology has proven to simplify administrative processes in education, including student enrollment. Currently, TK Islam Perkasa still relies on manual enrollment methods, involving paper-based forms, data verification, and document storage. This process often leads to various issues, such as document duplication, input errors, and inefficiencies in data retrieval and management. To address these challenges, a web-based enrollment information system integrated with a database has been designed. The system is developed using the Agile methodology, which allows for iterative and collaborative software development, ensuring user requirements are better accommodated. The PIECES analysis is employed to identify problems and propose solutions in terms of performance, information, economics, control, efficiency, and service aspects. The system is built using the Laravel framework and PHP programming language, with PostgreSQL as the database to support fast and accurate data management. This system enables online enrollment, saving time and effort for both prospective students and school administrators. Key features include digital form submission, automated data verification, and well-organized data storage and retrieval. The implementation of this system is expected to enhance administrative efficiency, reduce errors, and provide a better user experience. Therefore, this system serves as an innovative solution to support digital transformation in the education sector